E-Commerce Marketing Strategy & Industrial Packaging Design to Increase Profit for Bontang Manggrove Syrup Products in Tanjung Laut Indah Village, Bontang City - Anis Siti Nurrohkayati; M. Najeri Al Syahrin; Yulia Tri Kusumawati; Muhammad Khairul (Procedia of Engineering and Life Science, 2021)
The business industry of the product of the fruit syrup ovata mangrove is an effort belonging to Ibu Amirah, the head of the Fragrant Leaf group (Paguyuban usaha Mangrove village in Tanjung Laut Indah, South Bontang, Bontang City, East Kalimantan province. In the implementation of the activities successfully identified and resolved several problems of the partner namely processing, the provision of business tools processing of mangrove syrup, identification of packaging design shortage, advertisement production of mangrove fruit syrup in the e-site Commerce and demonstration of how to process e commerce and social media sites. In the overall stages of activity, the team of devotion also coordinates and interviews with the forestry service of the province of East Kalimantan which became the authorized institution in the management of the mangrove fruit syrup and its cultivation in the city of Bontang. Hopefully in this stage, partners can independently add products, conduct sales control, and use e commerce sites to the fullest without relying on the team.